Evaluation of the Effect of Oral Vitamin B1 on Pain Due to Corneal Neuropathy after Cataract Surgery - kermani, Bahareh; Kargar, Shiva; Ghasemi Nejad Afshar, Reza; Mehralizadeh, Akbar; Neshan, Mahdi; Yusefi, Ali Reza; Barfar, Eshagh; Sheikh Beig Goharrizi, Mohammad Ali; Daneshi, Salman (Journal of Ophthalmic and Optometric Sciences, 2022)
Introduction: Cataracts are the leading cause of low vision and blindness in the world, and the only effective treatment for cataract vision impairment is surgery, which has common complications such as eye pain and burning, inflammation, and postoperative headache. The aim of this study was to evaluate the effect of vitamin B1 on oral pain on corneal neuropathy after cataract surgery in Jiroft. Method and Materials: This randomized clinical trial study was performed on cataract patients who were candidates for surgery and referred to Imam Khomeini Hospital in Jiroft in 2020. Demographic information was collected through a designed checklist and the Numerical Pain Scale (NRS) was used to measure postoperative severity in the eye. The collected data were analyzed using SPSS-V21 software. Results: In this study, 130 patients with cataracts (intervention group: 65 and control group: 65) were studied. The intervention group consisted of 27 men (41.5 %) and 38 women (58.5 %) and the control group consisted of 25 men (38.5 %) and 40 women (61.5 %). On the third day and one week after surgery, there was no significant difference in the amount of eye pain and irritation caused by surgery in the intervention and control groups, and in the three months after surgery, the intervention group had mild eye pain and irritation.Conclusion: The results of this study showed that taking vitamin B1 orally affects eye irritation and pain caused by corneal neuropathy after cataract surgery and reduces eye irritation and pain intensity during 3 months.